2017
DOI: 10.1002/ange.201705356
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Amination with Nitroarenes

Abstract: An exceptionally general electrophilic amination, which directly transforms commercially available nitroarenes into alkylated aromatic aminoboranes with zinc organyl compounds was developed. The reaction starts with at wostep partial reduction of the nitro group to anitrenoid, whichis used in situ as the electrophilic amination reagent. To facilitate isolation, the resulting air-a nd moisture-sensitive aminoboranes were reacted with arange of electrophiles.The method not only represents ad irect transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Leveraging the utility of tricoordinate phosphorus reagents as O-atom acceptors [6], this chemistry advances a line of work from Cadogan who showed that P(III)-mediated deoxygenation of nitroarenes can give nitrogen containing heterocyclic products through intramolecular C-N bond formation ( Figure 1A) [7,8], Indeed, nitroarenes are attractive substrates for aryl amination reactions because they are readily available from both commercial and synthetic sources, thereby comparing favorably with respect to nitrosoarenes [9], N-alkyl hydroxylamines [10], azides [11], and tosyl triazenes [12] substrates for boronic acid amination reactions. Knochel [13], Kürti [14], and Niggemann [15] have all reported main group reagent approaches for direct intermolecular C-N bond formation with nitroarene substrates. Relatedly, Suárez-Pantiga and Sanz reported that phosphine-mediated reductive coupling of nitroarenes and boronic acids is catalyzed by an oxomolybdenum compound [16].…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the utility of tricoordinate phosphorus reagents as O-atom acceptors [6], this chemistry advances a line of work from Cadogan who showed that P(III)-mediated deoxygenation of nitroarenes can give nitrogen containing heterocyclic products through intramolecular C-N bond formation ( Figure 1A) [7,8], Indeed, nitroarenes are attractive substrates for aryl amination reactions because they are readily available from both commercial and synthetic sources, thereby comparing favorably with respect to nitrosoarenes [9], N-alkyl hydroxylamines [10], azides [11], and tosyl triazenes [12] substrates for boronic acid amination reactions. Knochel [13], Kürti [14], and Niggemann [15] have all reported main group reagent approaches for direct intermolecular C-N bond formation with nitroarene substrates. Relatedly, Suárez-Pantiga and Sanz reported that phosphine-mediated reductive coupling of nitroarenes and boronic acids is catalyzed by an oxomolybdenum compound [16].…”
Section: Introductionmentioning
confidence: 99%
“…this inexpensive and easily-handled liquid as a potential surrogate for methylamine-a gaseous List 1 controlled precursor 7 -especially in catalytic coupling chemistry (Figure 1A,right). [8][9][10][11] At present, reductive N-functionalization of H 3 C-NO 2 is limited to two isolated examples: Niggemann has reported reductive N-benzylation of nitromethane mediated by stoichiometric B 2 pin 2 in the presence of excess BnZnBr, 12 and Suarez-Pantiga and Sanz have reported a triphenylphosphine-mediated reductive N-phenylation of nitromethane catalyzed by an oxomolybdenum(VI) compound under microwave irradiation. 13 We report here a general catalytic method for the methylamination of arylboronic acids and esters with H 3 C-NO 2 by reductive C-N coupling driven by P III /P V =O redox cycling (Figure 1B).…”
mentioning
confidence: 99%
“…Niggemann et al reported a reductive coupling of nitroarenes with zinc organyl compounds for the production of alkylated arylamines using B 2 pin 2 as the O-atom acceptor (Scheme 4 ). 19 According to their mechanism, a nitronate intermediate was generated from the addition of B 2 pin 2 to the O atom of the nitro group, and then the boronic acid ester played the role of a reductant in reducing the nitronate to a nitrenoid which underwent C–N bond construction smoothly via an ‘addition–1,2-migration’ pathway with the organozinc compound. The generated aminoboranes were converted into the final amine products through hydrolytic work-up or by addition of an electrophile.…”
Section: Reductive Coupling Of Nitro Compounds With Organometallic Re...mentioning
confidence: 99%